Surf, sand, scrapes and stings: First aid incidents involving children at New Zealand beaches, 2007–2012. (10th December 2013) - Moran, Kevin; Webber, Jonathon
<x xml:space="preserve">Abstract</x> Aims In spite of the popularity of beaches for family recreation, little is known about childhood injuries sustained at beaches. It is the purpose of this study to analyse data from incidents necessitating first aid treatment from reports compiled by surf lifeguards on New Zealand beaches. Method A retrospective analysis of first aid incidents involving children (<16 years) was conducted using data obtained from Surf Life Saving New Zealand incident report forms during five summer seasons from 2007 to 2012. In addition to demographic data, the incident reports included such detail as the type of injury, the activity and location prior to injury, the injury outcome, and the first aid equipment used. Results Children (n = 4407) accounted for one‐half (52%) of all injuries; of these, 55% were male, and incidence peaked in the 11‐ to 15‐year age group (24%). Most incidents (90%) required minor treatment, with lacerations (44%) the most common injury. Marine stings accounted for one‐quarter (24%) of injuries and were most frequent among younger children (<10 years). Injuries to the extremities were frequently noted in the incident reports, the feet (33%) and hands (8%) being common sites. Conclusions Although most (90%) injury incidents were minor in nature, their frequency (880 cases per season) suggests that greater emphasis on prevention rather than cure would be efficacious. Ways of promoting child beach safety via greater care giver awareness, the use of protective clothing and footwear, and child safety promotion via health professionals and safety organisations are discussed.